A 14-Year Retrospective Analysis of Endogenous Endophthalmitis in a Tertiary Referral Center of Southern Thailand. (15th December 2020) - Bhurayanontachai, Patama; Klongthanakit, Phingphan
Abstract : Purpose . To investigate patient characteristics, clinical features, common causative organisms, and visual acuity outcomes in endogenous endophthalmitis. Methods . This was a retrospective chart analysis of patients with endogenous endophthalmitis between January 2006 and December 2019. Collected data included basic patient characteristics, presenting symptoms, causative organisms, treatments, and 3-month and 1-year visual outcomes. Results . Twenty-nine eyes of 27 patients were included in the study. The mean age of the patients was 45.4 ± 19.9 years, and 63% were female. Visual acuity at presentation ranged from counting fingers to no light perception. Systemic comorbidities presented in 66.7% of the patients, the majority of which were related to diabetes mellitus (48.1%). The most common primary infection was a urinary tract infection. Positive blood cultures were identified in 48.1% of patients, and positive cultures from vitreous and aqueous samples were identified in 59.3% and 31.6% of eyes, respectively. Among all the specimens, Gram-positive bacteria were identified in 55.5%, Gram-negative bacteria in 22.2%, fungi in 14.8%, and mixed organisms in 7.4%. Among ocular specimens, 61.1% contained Gram-positive organisms, 16.7% contained Gram-negative organisms, and 22.2% contained fungi. Streptococcus spp. was the most common causative organism. From 29 eyes, 18 (62.1%) underwent vitrectomy, and 12 (42.9%) underwent either evisceration or enucleation. Positive vitreous culture was significantly associated with unfavorable final visual outcome. Final visual acuity ranged from 20/125 to no light perception. Although visual improvement at 3 months was significantly better in younger patients, this had no impact on final visual outcome at 1 year. Conclusion . Eyes with positive vitreous cultures had significantly poorer visual outcomes. Despite full treatment coverage, visual prognosis was extremely poor and the rates of blindness and evisceration/enucleation were still high.